Pembelajaran Digital Dalam Menelaah Cerpen Dengan Menerapkan Metode Discovery Learning - I Gede Gita Wiastra; Kadek Ayu Kartika Septiana (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2023)
Language skills, such as studying short stories, are still perceived as difficult skills, because students do not know how to interpret the meaning of stories that occur in a short story. The purpose of this study is to contribute ideas/opinions in order to improve the ability to study the structure and language of short stories for students of class IX B State Junior High School 2 Tabanan in the 2021/2022 academic year. This research is a classroom action research which consists of two cycles with 38 students. Data collection methods used, namely the method of observation, test method and method of recording documents. Observation method was used to obtain data about students' attitudes and behavior. The test method is used to determine the students' ability in studying the structure and language of short stories. The data analysis method used is descriptive method. The results show that the ability to study the structure and language of short stories for class IX B students at State Junior High School 2 Tabanan in the 2021/2022 academic year by applying the discovery learning has increased. This is evident from the score in the pre-cycle class average of 61.84, then in the first cycle increased to 70.52, and in the second cycle increased to 81.57. The increase from pre-cycle to cycle I was 14.64%. The increase from cycle I to cycle II was 16.19. The average increase in cycle II reflects the students' understanding of the structure and language of short stories getting better. Based on the results of data analysis, it can be concluded that by applying the discovery learning students' abilities have increased. Thus, it is recommended for Indonesian language teachers to apply the discovery learning when learning about studying the structure and language of short stories because it has been proven that the application of the discovery learning can improve students' abilities.